PD-L1 Expression in Medullary Thyroid Carcinoma and Its Association with Clinicopathological Findings - Yasemin KEMAL; Sultan ÇALIŞKAN; Seda GUN; Mehmet KEFELI (Federation of Turkish Pathology Societies, 2022)
Objective: Medullary thyroid carcinoma (MTC) is a rare tumor originating from parafollicular C cells. It has more aggressive biologic behavior than differentiated thyroid carcinomas, and it is insensitive to treatment with radioactive iodine. Vandetanib and cabozantinib are the newly approved tyrosine kinase inhibitors in advanced stages, but novel effective systemic therapeutics could be crucial and needed for the clinical management of these patients. We aimed to evaluate the Programmed death-ligand 1 (PD-L1) expression, which is a novel immunotherapy target, in our MTC cohort, and determine whether it has an association with clinical and pathological features. Material and Method: This retrospective study involved 41 cases of MTC with a median follow-up of 54 months. PD-L1 monoclonal antibody (SP263 clone) was investigated immunohistochemically. Complete and/or partial membranous staining pattern in more than 1% of tumor cells was considered positive. The correlations of PD-L1 expression with clinicopathologic and prognostic features were analyzed. Results: PD-L1 positivity was detected in 5 (12.2%) of 41 tumors. The extent of PD-L1 staining was low (<5%) for all tumors. There was no clinicopathologic and prognostic relevance regarding PD-L1 expression in our MTC patients. Conclusion: Although PD-L1 expression could be a potential biomarker to predict the prognosis of various cancers and response to checkpoint inhibitors, we did not find any significant correlation between PD-L1 expression and clinicopathologic features in our cases. Studies with larger patient numbers are still required to perform a more comprehensive analysis.